2020
DOI: 10.26552/com.c.2020.2.97-106
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Acceptance Factor of Android-Based Parking Information Systems in Indonesia

Abstract: Parking is an unrelenting problem, with more vehicles having an impact on the way how to park a vehicle. Some experts have made various breakthroughs in overcoming parking problems; one of them is using smartphone technology as a system to facilitate the way to park. This study aims to analyse user acceptance using the Unified Theory of Acceptance and Use of Technology UTAUT method with structural equation models (SEM-PLS), against 221 respondents. The result is that performance expectations, effort expectancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
(58 reference statements)
0
4
0
3
Order By: Relevance
“…In addition to these primary factors, research has also highlighted latent variables, which are not directly observable, such as safety [22,23], privacy [24][25][26], attitudes [27,28], and social influence [29][30][31][32][33]. These latent variables are grounded in well-established theoretical frameworks, such as the theory of planned behavior (TPB), the technology acceptance model (TAM), and privacy calculus theory (PCT), which provide a solid foundation for exploring the relationships between these latent factors and parking intentions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to these primary factors, research has also highlighted latent variables, which are not directly observable, such as safety [22,23], privacy [24][25][26], attitudes [27,28], and social influence [29][30][31][32][33]. These latent variables are grounded in well-established theoretical frameworks, such as the theory of planned behavior (TPB), the technology acceptance model (TAM), and privacy calculus theory (PCT), which provide a solid foundation for exploring the relationships between these latent factors and parking intentions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hasil penelitian ini sejalan dengan hasil penelitian yang dilakukan oleh (Chen et al, 2021;Ilham et al, 2020;Martínez et al, 2018) yang menemukan bahwa Ekspektansi usaha secara positif mempengaruhi Ekspektansi kinerja. Selain itu hasil penelitian ini sejalan dengan UTAUT (Unified Theory of Acceptanc Use Technology) yang menjelaskan bahwa kemudahan penggunaan teknologi akan mempengaruhi kinerja yang pengguna.…”
Section: Akunesa : Jurnal Akuntansi Unesaunclassified
“…Berdasarkan penelitian terdahulu terdapat beberapa faktor yang mempengaruhi niat seseorang untuk menggunakan atau menerapkan teknologi. Menurut Model UTAUT, variabel ekspektansi kinerja, ekspektansi usaha dan pengaruh sosial mempengaruhi niat seseorang dalam menggunakan teknologi baru (Dajani & Abu Hegleh, 2019;Ilham et al, 2020Ilham et al, , 2021Siregar et al, 2021). Namun demikian masih terdapat hasil yang tidak konsisten antaara satu penelitian dengan penelitian lainnya.…”
unclassified
“…The sensor-based technologies in vehicles inside the urban spaces possess the quite a prominence regarding the parking purpose. Using the UTAUT, an Indonesian study towards urban parking technology acceptance showed the Facilitating Conditions as a key predictor among netizens [43]. More studies on parking technologies revealed that Perceived Usefulness with Perceived Network Externality in shared parking [44], Perceived Risk with role of gender for deciding the shared parking versus conventional parking [45] can play important part in adopting the smart parking tool.…”
Section: E100mentioning
confidence: 99%